Chromosomal evolution of South American Columbiformes (Aves) - De Lucca, E. J. [UNESP] (Kluwer Academic Publ, 1984)
Karyotypes are compared of 14 species of Brazilian Columbiformes (family Columbidae): Claravis pretiosa (2n=74), Columba cayennensis (2n=76), Columba picazuro (2n=76), Columba speciosa (2n=76), Columbina minuta (2n=76), Columbina passerina (2n=76), Columbina picui (2n=76), Columbina talpacoti (2n=76), Geotrygon montana (2n=86), Leptotila rufaxilla (2n=76), Leptotila verreauxi (2n=78), Scardafella squammata (2n=78), Uropelia campestris (2n=68) and Zenaida auriculata (2n=76). The macrochromosomes of each species were analysed by conventional Giemsa staining, cytobiometrically and with G-and C-banding. All species studied are characterized by typical bird karyotypes with a few pairs of macrochromosomes and many microchromosomes. The morphology and relative length of the Z chromosome are nearly the same in all species, but the W chromosome shows variation. The G-band patterns of the first pair in Columbiformes show a large positive band distally in the long arm, common to all species of the order. The constitutive heterochromatin is restricted to the centromeres of the macro- and microchromosomes. The W is the most heterochromatic chromosome in all species studied. Studies of relative lengths, arm ratios and G- and C-banding patterns showed that in Columbiformes pairs 3, 4 and 5 are the most stable. The types of rearrangements distinguishing between species vary among the genera: pericentric inversions in Columba; fusions and translocations in Uropelia; centric fissions in Geotrygon; fusions, translocations, para and pericentric inversions in Columbina, Leptotila, Zenaida and Scardafella. On the basis of the karyological findings the phylogenetic relationships of the Brazilian Columbiformes are discussed. © 1984 Dr W. Junk Publishers.